Tyrosinase inhibitory activity of Sargassum plagyophyllum and Eucheuma cottonii methanol extracts. (May 2019) - Dolorosa, M T; Nurjanah,; Purwaningsih, S; Anwar, E; Hidayat, T
Abstract: Tyrosinase is an enzyme that plays a role in the formation of melanin on two reactions, namely monophenolase and diphenolase. The process of melanin formation can be reduced through the inhibition mechanism of the tyrosinase enzyme. Seaweeds are natural organisms that have recognized lightening agents. Sargassum plagyophyllum contains secondary metabolite compounds such as alkaloids, steroids, flavonoids, saponins, and tannins while Eucheuma cottonii contains alkaloids and terpenoids. The aim of this research was to determine the tyrosinase inhibitory activity of seaweeds. The yield of methanol extract amounted to 1.342% in S. plagyophyllum and 0.2599% in E. cottonii. The inhibitory activity of tyrosine is performed by measuring enzymatic reaction using L-tyrosine (monophenolase) and L-DOPA (diphenolase) substrates and presented as IC50 value. The IC50 values of kojic acid as a positive control were 15.566 μg/mL for monophenolase and 29.156 μg/mL for diphenolase. The IC50 values of S. plagyophyllum and E. cottonii methanol extracts for monophenolase were 2195.206 μg/mL and 2691.478 μg/mL, respectively. The IC50 value of methanol extract was 1769.336 μg/mL for S. plagyophyllum and 2631.648 μg/mL for E. cottonii on diphenolase. Methanol extracts from these two species of seaweed have the potential to be developed as bioactive compounds in skin lightening cosmetics.